Efectividad de las medidas de protección de la violencia contra la mujer en el Centro de Emergencia Mujer Iquitos –Loreto–2020 - Quinteros Davila, Romulo Angel (2024)
The main objective of the study "Effectiveness of Protective Measures Against Violence Against Women at the Women's Emergency Center of Iquitos, Loreto Province" is to evaluate the effectiveness of protective measures for victims of violence against women at the center level. This study was conducted using a quantitative approach and had a baseline and descriptive design. The study population included 100 cases of violence against women reported by the CEM, covering 100% of the total population. Data were collected through methods such as surveys, direct observation, and document analysis. Finally, the study concludes that the protective measures established by the Women's Commission of the Municipality of Iquitos in favor of women victims of domestic violence are effective, successfully achieving the protection and security of the complainant and guaranteeing her physical and mental health. However, it is essential to reinforce women's knowledge about the protective measures available to them. This can be achieved through the development of training workshops and dissemination via radio, print, and television, managed by authorities at all levels of government, as well as judicial authorities in Peru, the Public Ministry, the National Police, and other public or private institutions.